IoT-Based Automatic Clothesline System Using ESP8266 with Fuzzy Logic Control and Web-Based Monitoring - Firda Ayu Adhidta; I Gede Puja Astawa; Faridatun Nadziroh (AI Society & STMIK Indonesia, 2026)
The efficiency and safety of manual clothes drying are significantly affected by weather conditions, such as rainfall, humidity, and limited sunlight. To address these challenges, this study presents the design and implementation of an Internet of Things (IoT)-based automatic clothesline system that uses an ESP8266 microcontroller with fuzzy logic control. The system incorporates multiple environmental parameters, including temperature, humidity, light intensity, and rain detection, to enable adaptive movement of the clothesline and fan activation. A fuzzy inference mechanism handles sensor data uncertainty and generates appropriate control actions in real time. Additionally, a web-based monitoring interface enables users to remotely monitor environmental conditions and system status and to manually control the system. Experimental results show that the system responds effectively to dynamic weather changes, reducing the risk of clothes being exposed to rain and enhancing overall drying efficiency. These findings suggest that the proposed approach offers a practical and reliable solution for smart household automation applications.